Assessment of bioelectrical impedance analysis for determining dry weight in pediatric hemodialysis patients; single center experience (Annals of Medical Research, 2021)
None
Keywords: Hemodialysis; Dry weight; Bioimpedance spectroscopy; Pediatrics.